La professionalità educativa in ambito penitenziario. L'Educatore e il suo ruolo pedagogico - Maria Rita Mancaniello (Firenze University Press, 2017)
The role of the educator in the penitentiary context is central to making the prin-ciple of imprisonment as rehabilitative in accordance with Art. 27 of the Italian Constitution. Difficult and complex role, that demands a strong pedagogical competence and must aim at the design of a new existence. An educational project that requires you to focus on the relationship between educator and person in custody and that focuses on the process of change the subject and its potential autopoietic.